MANAGEMENT OF THE QUALITY CHARACTERISTICS OF LABRADORITE PRODUCTS OF THE UKRAINIAN SHIELD TAKING INTO ACCOUNT THE TYPES OF THEIR SURFACE PROCESSING - GELETA, Oleg; SERGIIENKO, Igor (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. Durability is one of the key characteristics of decorative stone, as it determines the service life of products made from this material. It depends not only on the petrographic composition of the stone but also on the type of surface texture treatment. Labradorite, a variety of anorthosite, is widely used in construction and decorative finishing due to its strength and frost resistance. Different surface treatment methods for labradorite products, such as thermal treatment, abrasive blasting, and water jet treatment, enhance not only the aesthetic properties of the stone but also its functionality, particularly its anti-slip characteristics. The study of these treatment methods is essential for determining their impact on the durability of decorative stone products.Methods. A series of experiments were carried out as part of this research using equipment specified in the DSTU B EN 13755:2007 "Methods of Testing Natural Stone. Determination of Water Absorption under Atmospheric Pressure" and an electronic ultrasonic piezoelectric flaw detector MATEST С372N.Results. The impact of several types of anti-slip surface treatments on the durability of labradorite products from two deposits of the Ukrainian Shield has been studied in detail. Durability is one of the key consumer characteristics of the quality of stone finishing materials. The research aimed to identify the correlation between increased water absorption and deterioration of stone preservation, depending on the applied surface treatments of labradorite samples from the Kamiana Pich and Slobidske deposits–abrasive blasting, water jet treatment under pressure, and thermal treatment (fire treatment). Laboratory studies showed that water jet treatment is the least destructive, while thermal treatment and abrasive blasting significantly impair the physico-mechanical properties of labradorite, increasing its water absorption and reducing its durability.Conclusions. The results of the research highlight the need for a well-founded choice of treatment technology based on the conditions of further use. These aspects should be considered not only at the stage of selecting decorative stone material but also during the design and implementation of architectural solutions, as the durability of natural stone products will influence the overall aesthetics and functionality of the architectural object. The obtained data are important for the informed selection of stone treatment technologies in construction and architecture, ensuring a balance between aesthetic properties and the operational stability of the material.
Keywords: labradorite; type of surface treatment; decorative stones; Ukrainian shield; water jet treatment; blast treatment; fire firing; heat treatment